2018
DOI: 10.1080/09546553.2018.1520702
|View full text |Cite
|
Sign up to set email alerts
|

Building “Terrorism Studies” as an Interdisciplinary Space: Addressing Recurring Issues in the Study of Terrorism

Abstract: Over the years, there have been many debates regarding the state of research into terrorism and whether "terrorism studies" constitutes an academic discipline in its own right. Such reflections, coupled with the natural evolution of what is still a relatively new area of research, have arguably led to significant improvements in quality and rigour. At the same time, the status of terrorism studies itself remains somewhat ambiguous: it is both discussed as a distinct field and simultaneously evades criticism by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Hopefully, this will serve to broaden the field's topical focus by bringing about greater attention for developments among non-jihadist extremist and terrorist groups, as well as for states own roles in using or supporting terrorism. Again, the point is by no means that it is wrong to pursue state-funded research or to focus on groups like al-Qaeda, but researchers should more carefully assess what the potential side effects of pursuing government-aligned research agendas could be, for instance in terms of promulgating one-sided perception of what terrorism is (Youngman 2018). Not just because these can impute one-sidedness into the academic debate, but because how terrorism is perceived and discussed by politicians, the media and pundits has much broader and far-reaching societal implications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hopefully, this will serve to broaden the field's topical focus by bringing about greater attention for developments among non-jihadist extremist and terrorist groups, as well as for states own roles in using or supporting terrorism. Again, the point is by no means that it is wrong to pursue state-funded research or to focus on groups like al-Qaeda, but researchers should more carefully assess what the potential side effects of pursuing government-aligned research agendas could be, for instance in terms of promulgating one-sided perception of what terrorism is (Youngman 2018). Not just because these can impute one-sidedness into the academic debate, but because how terrorism is perceived and discussed by politicians, the media and pundits has much broader and far-reaching societal implications.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, none of these points are particularly novel. Terrorism researchers have been raising these issues for years (Ranstorp 2007;Silke 2004a;Youngman 2018). So why do they persist?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McCauley and Moskalenko briefly reviewed the literature since 9/11 and suggested that steady progress in this area is being made. This view has been echoed by others (Gill & Corner, 2017;Gruenewald, Chermak, & Freilich, 2013;Schuurman, 2018;Silke & Schmidt-Petersen, 2017;Stern, 2014;Taylor, 2014;Youngman, 2018), and there have been a number of studies published since 2014 that have applied empirical methods to examine realworld data, for example, via the collation and analysis of open source data (e.g. Corner & Gill, 2015;Ellis et al, 2016;Knight, Woodward, & Lancaster, 2017).…”
Section: Section One: Advances In Empirical Researchmentioning
confidence: 99%
“…The reviewing committee must ensure that they are set-up to adequately and appropriately review the ethical nature of research in this area. For those individual institutional IRBs/HRECs that do not have the adequate institutional knowledge, or training, to appropriately review terrorism research proposals, the establishment of cross-institutional advisory mechanisms 52 and national IRBs 53 have been mooted to assist in the review processes. It has been proposed that such mechanisms can greatly assist in the development and application of appropriate expertise.…”
Section: The Ethical Review Process and Board Membershipmentioning
confidence: 99%